Enantioselective synthesis of GNE-6688, a potent and selective inhibitor of interleukin-2 inducible T-cell kinase (ITK). Issue 11 (14th March 2019) - Moore, Jared; Lau, Kevin; Xu, Xiaofeng; Zhang, Yamin; Burch, Jason D.
Graphical abstract: Highlights: A stereoselective synthesis of the ITK inhibitor GNE-6688 has been accomplished. An enantioselective transfer hydrogenation was used to prepare the Western fragment. An enantioselective allylboration, and a directed cyclopropanation were key steps for the Eastern fragment. Abstract: An enantioselective synthesis of the previously-disclosed ITK inhibitor GNE-6688 is described. Synthesis of the nitropyrazole fragment is highlighted by a Ru-catalyzed transfer hydrogenation using the Wills tethered ligand system. Synthesis of the pyrazole carboxylic acid fragment features an allylboration catalyzed by a chiral diol-SnCl4 complex, followed by a highly diastereoselective directed cyclopropanation.